REPRESENTASI MASYARAKAT KONSUMSI PADA FILM MR. BEAN’S HOLIDAY - Sasi, Ingga Amara; Nugroho, Wahyu Budi; Kebayantini, Ni Luh Nyoman (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT Mr. Bean ’s Holiday is a family comedy movie that includes a representation of the consumer society with the main character, Rowan Atkinson as Mr. Bean. Representation of consumption society in the Mr. Bean ’s Holiday movie is shown through the product placement shown in several scenes. Product placement is defined as a product message that is paid with the aim to influencing the audience through a planned coverage of a product into the movie. This study examined the representation of consumption society through the product placement in the movie Mr. Bean's Holiday uses the perspective from Jean Baudrillard's consumption society. This movie was analyzed by using Jean Baudrillard's semiotic analysis technique. The results showed the product placement displayed in the movie Mr. Bean's Holiday is able to convey the codes that make up the message well, which in turn is able to develop people's impressions. In addition, the existence of product placement is able to influence audiences lived in a simulated world where is formed through the relationship of various signs and codes. Baudrillard emphasizes that consumerism is formed through the use value which changes into a sign value. Changes in value to use become a sign of value due to the influence of the mass media that distributes codes and messages which are then more trusted by the public. Therefore, product placement has a big contribution to the delivering message of a product that ultimately makes people like the meaning of the product that changes society more consumptively. Keywords: consumer society, product placement, media